EKSPLORASI STRATEGI GURU DALAM MENGEMBANGKAN INSTRUMEN EVALUASI FORMATIF PADA PEMBELAJARAN MATEMATIKA DI SMP - Diana Lestari, Rina; Prasetyono, Hendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Formative assessment plays a very important role in the learning process because it provides continuous feedback for both teachers and students in improving learning strategies and enhancing learning outcomes. In mathematics learning at the junior high school level, effective formative assessment instruments are urgently needed so that students' understanding of concepts and problem-solving skills can be measured comprehensively. This study aims to explore teachers' strategies in developing formative assessment instruments in mathematics learning at junior high school. The research method used is a qualitative approach with an exploratory design through a literature review. Data collection was carried out by reviewing relevant journal articles, books, and research reports, which were then analyzed through the stages of literature selection, information reduction, strategy categorization, and synthesis. The results of the study indicate that teachers use various strategies in designing formative evaluation instruments, including the use of pre-tests to measure initial readiness, formative tests in the form of essay questions or contextual quizzes to assess conceptual understanding, post-tests to review final achievements, and observation of student activities, group discussions, and problem-based tasks to assess engagement and critical thinking skills with the use of concrete media and rewards. Based on this, the development of innovative, structured formative evaluation instruments followed by remedial and enrichment follow-up is essential to make mathematics learning in junior high schools more adaptive, reflective, and oriented towards improving the quality of student learning outcomes.